Blanca Paula RODRÍGUEZ GARABATOS, "Emilia Pardo Bazán: Visiones del dandismo". A Coruña, Hércules, 2021, 156 pp. - Rozados Fernández, Marian (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
In this book about the narrative work of Emilia Pardo Bazán, Blanca Paula Rodríguez Garabatos reveals the passion of the writer from A Coruña for decadent literature and the different experiments she carried out in her stories and novels to try to capture the physiognomy and psychology of dandyism. a vital and aesthetic attitude always within the limits of morality.
Keywords: Emilia Pardo Bazán; Spanish Literature; European Literature; dandysm; pardobazanian narrative